Does participative management produce satisfied employees? Evidence from the automotive industry - Stefanovska, Miodraga; Bojadzijev, Marjan; Mucunski, Zlatko (Serbian Journal of Management, 2015)
The effect of participative management on job satisfaction was examined in an automotive sales company in Macedonia. The information was collected from 150 employees. Three components of participatory management was analyzed in the research (1) participatory management style (2) participatory strategic planning process and (3) effective supervisory communication. Results showed that there was a positive relationship between all three components of participatory management and job satisfaction. The relationship between participatory management and job satisfaction was analyzed using statistical methods to determine the correlations and OLS regression model. The study highlights methodological developments in determining the effect of participatory management on job satisfaction in the automotive sales industry. The findings suggest that there is a positive relationship between both and it is therefore important to sustain these factors in order to maintain employees’ motivation.